Roman pottery production in Civitas Tungrorum, central Belgium, during the first–third centuries ce. (19th December 2019) - Borgers, B.; Quinn, P.; Degryse, P.; De Bie, M.; Welkenhuysen, K.
Abstract : Aspects of Roman pottery production at the workshops of Kontich, Tienen, Rumst, Grobbendonk and Clavier‐Vervoz in the Civitas Tungrorum of central Belgium are explored. A total of 150 wasters from five sites were studied macroscopically, as well as via a combination of thin‐section petrography, geochemistry and scanning electron microscopy, in order to gain insights into ceramic technology and aspects of the organization of production. Particular emphasis was given to the individual technological sequences and shared strategies of raw material selection, paste preparation and firing employed at the five adjacent sites. The integration of petrographic and geochemical data permitted the establishment of compositional reference groups for the Roman kiln sites of Civitas Tungrorum, which can be used to track their products within the surrounding landscape.